Evaluation of IT Governance With a Focus on Business Application Continuity Using the Cobit 2019 Framework : A Case Study in XYZ Group - Bagus Firmansyah; Heru Purnomo Ipung; Mohammad A Soetomo (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2025)
This study aims to evaluate the current state of IT governance at XYZ Group, identify capability gaps against best practices, and propose an improved governance model based on the COBIT 2019 framework. A mixed-method approach was applied, combining qualitative interviews with IT stakeholders and quantitative capability assessments across key governance objectives, including EDM03 (Ensured Risk Optimization), APO12 (Managed Risk), APO13 (Managed Security), BAI10 (Managed Configuration), DSS04 (Managed Continuity), and DSS05 (Managed Security Services). The capability assessment revealed that governance all process areas are at a capability level 2 Partially Achieved and lowest with EDM03 scoring 11.1%, indicating the process is not yet achieved according to COBIT 2019 standards. To validate the proposed governance framework, a validation was conducted involving both academic and industry experts. The results confirmed that the framework is relevant, feasible, and strategically aligned with XYZ Group’s IT goals. This research contributes a tailored governance solution focused on strengthening business application continuity, offering a practical reference for mid-sized organizations navigating similar challenges.